Singing thieves: history and practice in Nigerian popular justice - Pratten, D (Hurst & Company, 2007)
Vigilantes and organised vigilantism are a growing phenomenon, as this book amply demonstrates. From Northern Ireland to West Africa, from Bombay or Moscow, vigilante movements and ideologies have widespread appeal.